Simulation of electromagnetic processes in the grounding system with a short circuit in the operating high-voltage substation - Koliushko, D. G.; Rudenko, S. S.; Istomin, O. Ye.; Saliba, A. N. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2022)
The aim of the work is a test of the developed mathematical model of electromagnetic processes of short circuit and approbation of the created software complex «LiGro» on its basis for the existing grounding system located in three-layer soil. Methodology. To improve the accuracy of calculating the normalized parameters of operating power stations and substations, the authors developed the «LiGro» software package based on the expressions obtained in for calculating the potential of the electric field of a non-equipotential grounding system (GS). To monitor the state and assess the efficiency of the GS of operating power facilities, the electromagnetic diagnostics is used. The topology of the GS was determined with the induction method by complex KNTR-1, the geoelectric structure of the soil was determined by the method of vertical electrical sounding using the Wenner installation, the interpretation of the sounding results was made by the «VEZ-4A» program. The calculation results show that for the selected substation, the model developed in the «LiGro» complex has a deviation δ2 from the experimental values Ut by an average of 8,2 %, and the model implemented in Grounding 1.0 (IEEE model) δ1 is 17,2 %. Originality. The results of the study confirm the adequacy of the developed GS model in the «LiGro» complex based on a three-layer soil model, with the experimental values of the touch voltage obtained by simulating a single-phase ground fault on a real GS in operation. The first time was made approbation of the «LiGro» software package when performing the EMD of the GS of an operating substation with a voltage class of 150 kV. Practical significance. The program software can be used by special measuring’s laboratory to determining electrical safety parameters: touch voltage, GS voltage, and GS resistance.